Shifts in growth light optima among diatom species support their succession during the spring bloom in the Arctic. (15th April 2022) - Croteau, Dany; Lacour, Thomas; Schiffrine, Nicolas; Morin, Philippe‐Israël; Forget, Marie‐Hélène; Bruyant, Flavienne; Ferland, Joannie; Lafond, Augustin; Campbell, Douglas A.; Tremblay, Jean‐Éric; Babin, Marcel; Lavaud, Johann
Abstract: Diatoms of the Arctic Ocean annually experience extreme changes of light environment linked to photoperiodic cycles and seasonal variations of the snow and sea‐ice cover extent and thickness which attenuate light penetration in the water column. Arctic diatom communities exploit this complex seasonal dynamic through a well‐documented species succession during spring, beginning in sea‐ice and culminating in massive phytoplankton blooms underneath sea‐ice and in the marginal ice zone. The pattern of diatom taxa sequentially dominating this succession is relatively well conserved interannually, and taxonomic shifts seem to align with habitat transitions. To understand whether differential photoadaptation strategies among diatom taxa explain these recurring succession sequences, we coupled laboratory experiments with field work in Baffin Bay at 67.5°N. Based on field data, we selected five diatom species typical of different ecological niches and measured their growth rates under light intensity ranges representative of their natural habitats. To characterize their photoacclimative responses, we sampled pigments and total particulate carbon, and conducted 14 C‐uptake photosynthesis response curves and variable fluorescence measurements. We documented a gradient in species respective light intensity for maximal growth suggesting divergent light response plasticity, which for the most part align with species sequential dominance. Other photophysiological parameters supported this ecophysiological framing, although contrasts were always clear only between succession endmembers, Nitzschia frigida and Chaetoceros neogracilis . To validate that these photoacclimative responses are representative of in situ dynamics, we compared them to the chlorophyll a ‐specific light‐limited slope ( α *) and saturated rate of photosynthesis ( P M * ), monitored in Baffin Bay on sea‐ice and planktonic communities. This complementary approach confirmed that unusual responses in α * and P M * as a function of light history intensity are similar between sentinel sympagic species N. frigida and natural ice‐core communities. While no light‐history‐dependent trends were observed in planktonic communities, their α * and P M * values were in the range of measurements from our monospecific cultures. Synthesis . Our results suggest that Arctic diatoms species photoadaptation strategy is tuned to the light environment of the habitats in which they dominate and indeed drives the seasonal taxonomic succession. Abstract : Our results suggest that Arctic diatoms species photoadaptation strategy is tuned to the light environment of the habitats in which they dominate and indeed drives the seasonal taxonomic succession. Résumé: Les microalgues diatomées de l'Océan Arctique subissent annuellement des changements extrêmes d'environnement lumineux, engendrés par les cycles saisonniers de photopériode et d'épaisseur et d'étendu du couvert de glace enneigé qui atténue la pénétration de la lumière dans la colonne d'eau. Les diatomées arctiques exploitent cette dynamique saisonnière complexe au fil d'une succession taxonomique saisonnière, qui débute au printemps dans la glace de mer et culmine sous, et à la lisière, de la banquise avec des floraisons phytoplanctoniques massives. La séquence de succession des taxons est relativement bien conservée inter‐annuellement et semble correspondent globalement aux transitions d'habitats (glace de mer, eau sous la glace, lisière de banquise et eaux libres). Afin de déterminer si, parmi les différents taxons, des contrastes de stratégies photoadaptatives supportent cette dynamique récurrente, nous avons combiné expériences en laboratoire et travail sur le terrain réalisé en baie de Baffin (67.5°N). En nous basant sur les données in situ, nous avons sélectionné cinq espèces de diatomées typiques de différentes niches écologiques et nous avons mesuré leurs taux de croissance sous différentes intensités lumineuses représentatives de leurs habitats naturels. Pour caractériser leur photoacclimatation, nous avons déterminé leur contenu en pigments et en carbone, réalisé des courbes de fixation photosynthétique de 14 C, et mesuré leur fluorescence chlorophyllienne variable. Nos résultats révèlent un gradient d'intensité lumineuse optimale de croissance entre les différentes espèces, en grande partie fidèle à leur séquence de dominance saisonnière in situ. D'autres paramètres photophysiologiques supportent également un gradient d'adaptation vers des lumières plus élevées chez les espèces abondantes en eaux libres, avec des contrastes plus marqués chez les espèces dominantes aux extrêmes de la succession. Notre approche complémentaire entre expérimentations en laboratoire et in situ indique également que les paramètres de fixation photosynthétique de 14 C de l'espèce sympagique modèle, Nitzschia frigida, et des communautés de microalgues prélevées dans la glace de mer, varient de façon similaire dépendamment de leur historique lumineux précédant les mesures. Synthèse. Nos résultats suggèrent que les espèces de diatomées arctiques ont acquis des stratégies de réponse à la lumière adaptées à l'environnement lumineux où elles dominent, ce qui supporte leur succession taxonomique saisonnière.